Dietary biomarkers and food records indicate compliance to study diets in the ADIRA (Anti-inflammatory Diet In Rheumatoid Arthritis) trial - Wadell, Anna Turesson; Bärebring, Linnea; Hulander, Erik; Gjertsson, Inger; Landberg, Rikard; Lindqvist, Helen; Winkvist, Anna (Frontiers in Nutrition, 2023)
Background: In the ADIRA (Anti-inflammatory Diet In Rheumatoid arthritis) trial, compliance to the study diets has previously been described primarily with a score based on reported intake of trial foods from telephone interviews. The aim of this study was to evaluate compliance using objective dietary biomarkers for whole grain, fruit and vegetables, margarine and oil, seafood and overall fat quality, as well as reported intake from food records of key components of the study diets. Methods: Fifty patients with rheumatoid arthritis were randomized to begin with the intervention diet (rich in whole grain, fruit and vegetables, margarine/oil and seafood) or the control diet (rich in meat and high-fat dairy) for 10 wks, followed by a ~4 mo wash-out period, and then switched diet. Compliance was evaluated using plasma alkylresorcinols (AR) as biomarkers for intake of whole grain wheat and rye, serum carotenoids for fruit and vegetables, plasma linoleic acid (LA, 18:2 n-6) and -α-linolenic acid (18:3, n-3) for margarine and cooking oil, plasma eicosapentaenoic acid (EPA, 20:5 n-3), -docosahexaenoic acid (DHA 22:6, n-3) and -docosapentaenoic acid (22:5 n-3) for seafood, and plasma fatty acid pattern for the overall dietary fat quality. Reported intake of whole grain, fruit, berries and vegetables, seafood, red meat, and fat quality was extracted from 3-d food records. Results: Plasma AR C21:0 and C23:0, LA, EPA, and DHA were higher while total serum carotenoids were lower after the intervention diet period compared to the control diet period (AR and carotenoids: P=<0.05, fatty acids: P=<0.001). Reported intake of whole grain, fruit, berries and vegetables, and seafood was higher and reported intake of red meat was lower during the intervention diet period compared to the control diet period (P=<0.001). Plasma- and reported fatty acid pattern differed as intended between the diet periods. Conclusion: This study indicates that the participants in the ADIRA trial were compliant to the study diets regarding intake of whole grain, cooking fat, seafood, and red meat, and the intended overall dietary fat quality. Compliance to instructions on fruit- and vegetable intake remains uncertain. Trial registration: NCT02941055 https://clinicaltrials.gov/ct2/show/NCT02941055?term=NCT02941055&draw=2&rank=1.